Isolation and Identification of Gram-Negative Bacteria on Cattle Farms Indicated by Mastitis - Siti Rani Ayuti; Zahwa Amelia Pratiwi; Masda Admi; Darniati Darniati; M Isa; Herrialfian Herrialfian (The International Journal of Tropical Veterinary and Biomedical Research, 2022)
Mastitis is one  of the causes  of diseases that can reduce livestock production.  Mastitis can be caused by various types of bacteria that cause a decrease in livestock production that is difficult to cure with antibiotics has been reported resistance. This study aims to determine gram-negative bacteria that can be the cause of mastitis in cows. The study used samples taken from folk farms by means of livestock udder swabs. Bacterial isolation is carried out by  planting in Mannitol Salt Agar (MSA) media  and identifying by Gram staining  and  biochemical tests (maltose and lactose). The data analysis used is descriptive analysis, namely the types of bacteria as the causative agents of mastitis.  The results of the study obtained bacteria that cause mastitis of  gram-negative species Klebsiella  sp and Enterobacter sp yang classified as Gram-negative  bacteria. It can be concluded that in cows indicated mastitis there are Gram-negative bacteria, these are morphologically identified, namely Klebsiella  sp and Enterobacter sp.